PENGARUH SPESIFIKASI PENUGASAN TERHADAP REKOMENDASI MENGHENTIKAN PROYEK YANG BERKINERJA BURUK DALAM MENCEGAH ESKALASI KOMITMEN MANAJERIAL: SEBUAH PERAN REPRESENTASI MENTAL - Camelia Verahastuti (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
Based on psychological theories about the creation and use of mental representations, and synthesize theory with the theory of decision making to develop the cognitive explanation of escalation behavior among consultants, this study investigates the effect of the assignment specifications on recommendations discontinuing of a poorly performing project in preventing managerial escalation of commitment the role of mental representation. Subjects consist of 102 undergraduate accounting students at Gadjah Mada University, Yogyakarta. This research was conducted using two experimental. First experimental research design used 3 x 1 (special purpose, special purpose alternative, general purpose; scores of knowledge) to examine the purpose of the assignment of mental representation. Experiment I manipulated into three assigned conditions: a special purpose, special alternative purpose and general purpose. In experiment II study using 2 x 2 factorial design (justification requirement, no justification requirement; general purpose, special purpose) to examine the effects of justification on the recommendation of the continuity of projects such as those used by Kadous and Sedor (2004). This study predicts that the purpose of processing information (assigned purpose) will influence the mental representations they build, process and store information, which ultimately affect their recommendation for the discontinuing recommendation of a poorly performing projects. The results showed that the specifications of the assignment against the recommendation to discontinuing recommendation of a poorly performing projects with the role of mental representation, can not prevent the escalation of commitment, unless given specific objectives in the assignment.